Evaluating an oral health education program for Korean soldiers during the COVID-19 era: Applying quantitative light-induced fluorescent technology—A pilot study - Youmi Kim; Sojung Mun (Photodiagnosis and Photodynamic Therapy)
Purpose: This study aimed to provide a basis for the development of a remote oral health education program for soldiers enlisted during the COVID-19 era(August–September 2021) by conducting oral health education using quantitative light-induced fluorescent technology and then comparing Quigley-Hein Plaque Index (QHPI) and oral health knowledge, awareness, and behavior. Methods: Thirty soldiers serving in a military hospital in South Korea were classified into two groups using simple random sampling. The experimental group implemented oral health education and self-managed using quantitative light-induced fluorescent technology, whereas the control group implemented oral health education alone. It was performed for 8 weeks at 2-week intervals. Thereafter, oral health knowledge, awareness, and behavior were surveyed, and QHPI was measured. Changes between and within groups over time were analyzed. Results: QHPI was statistically significantly reduced in the experimental group over time. Oral health knowledge, awareness, and behavior scores were higher in the experimental group than in the control group, with statistically significant differences. Oral health education considering the characteristics of soldiers, who utilized quantitative light-induced fluorescent technology, was shown to be effective, and this effect requires further research through a longitudinal study. Conclusion: This study demonstrated that oral health education based on quantitative light-induced fluorescent technology should be a useful tool for improving the oral hygiene status, oral health knowledge, awareness, and behavior of Korean soldiers.